The Qur’anic Parables and Cinema - (:unkn) unknown (My University, 2019)
Almighty Allah created the universe and specially man as a wonder of art. Allah is unique in creation. Theshape and functioning of the universe has a complete aesthetic, and man himself is created in completeaesthetic perfection. The last sacred book that was created with the beauty of aesthetics and art was sent asa literary masterpiece. Inspired by the Qur’an, man can offer this beauty phenomenon to the multi-facetedbenefit. One of them should be an attempt to stage the parables of the Qur’an.The Qur’an uses different literary methods to convey its message. For example; representation (temsil),simile (teşbih), repetition (tekrir), concision (icaz), miraculously (i’caz), eupheism (itnab) and parable(kıssa) methods are some of them. One of the most noteworthy of these methods is to give a message through the parable. The Qur’an contains parables in a quarter of its content. In other words, a quarter of theQur’an consists of parables.In recent times, we see that the parables in the sacred texts are being adapted to the cinema. Unfortunately,we do not see the same effort in the Qur’anic parables. However, there is a serious material in this sense inthe Qur’an. Therefore, there is a need to work in this field. This article will contribute to those who wantto work in this open field.

Yüce Allah evreni ve özel olarak insanı bir sanat harikası olarak yaratmıştır. Allah (cc) yaratmada_x000D_ eşsizdir. Evrenin şekli ve işleyişi eksiksiz bir estetiğe sahip olduğu gibi insanın kendisi de tam bir_x000D_ estetik mükemmellik içinde yaratılmıştır. Estetik ve sanat güzelliğiyle yaratılan insanoğluna son_x000D_ ilahi kitap da bir edebi şaheser olarak gönderilmiştir. O, içinde yaratıldığı bu güzellik olgusunu_x000D_ Kur’an’dan aldığı ilhamla çok yönlü olarak istifadeye sunabilir. Bunlardan biri de Kur’an kıssalarını sahneye çıkarma çabası olmalıdır._x000D_ Kur’an-ı Kerim mesajını iletmede farklı edebi metotlar kullanır. Örneğin temsil, teşbih, tekrir,_x000D_ i’caz, icaz, itnab ve kıssa yöntemleri bunlardan bazılarıdır. Bunlar içerisinde en dikkat çekenlerden biri de kıssa yoluyla mesajı arz etmektir. Kur’an, muhtevasında kıssalara dörtte bir oranında_x000D_ yer vermektedir. Diğer bir ifadeyle Kur’an’ın dörtte biri kıssalardan meydana gelmektedir._x000D_ Son dönemlerde kutsal metinlerdeki kıssaların sinemaya uyarlanmaya başlandığına şahit olmaktayız. Ne var ki Kur’an kıssaları konusunda aynı çabayı göremiyoruz. Halbuki Kur’an’da bu_x000D_ anlamda ciddi oranda materyal bulunmaktadır. O halde bu alanda çalışma yapmaya ihtiyaç vardır._x000D_ Makalemiz, işte bu açık alanda çalışma yapmak isteyenlere katkı sağlayabilir
Kur’an Kıssaları ve Sinema